The syntheses and photophysical properties of 4,4′-isopropylidendioxydiphenyl substituted ball-type dinuclear Mg(II) and Zn(II) phthalocyanines - Canlica, Mevlude; Nyokong, Tebello (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
The syntheses of ball-type dinuclear Zn(II) and Mg(II) phthalocyanines containing four 4,4'-isopropylidendioxydiphenyl substituents at the peripheral and non-peripheral positions are presented. The structures of the synthesized compounds were characterized using elemental analyses, and UV-Vis, FT-IR, H-1 NMR and mass spectroscopies. The phi(F) values were 0.14, 0.11, 0.22, 0.15 and phi(T) values were 0.84, 0.88, 0.62, 0.74, for 6-9, respectively. The largest triplet yields were observed for the non-peripherally substituted complexes 6 and 7, showing that non-peripheral substitution favors increased population of the triplet state. All complexes showed reasonably long triplet lifetimes with tau(T) 510, 310, 910 and 350 mu s in DMSO, respectively. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Mg ball-type phthalocyanine; Zn ball-type phthalocyanine; Photodynamic therapy; Non-peripheral phthalocyanine; Triplet quantum yield; ZINC PHTHALOCYANINES; 1,2-BIS(3,4-DICYANOPHENOXYMETHYL)BENZENE; METALLOPHTHALOCYANINES; DERIVATIVES; CLAMSHELL; CO; Chemistry; Crystallography